Business Potential of Garam Manis Company - Zonia, Veby Lin; Aldianto, Leo (Journal of Business and Management, 2014)
Garam Manis Company is a start-up company that created the technology that can produce industrial salt with standards industry by using electrolysis, evaporation and geomembrane. In relation to the lack of technology that could produce the industrial salt in Indonesia and the high demand for industrial salt in Indonesia, 1.8 million tons / year, there is one innovation generated by Start-up Company that is Garam Manis Company. The new technologies using electrolysis, evaporation, and geomembrane that can produce quality crystal salt products meet the quality standards of industrial salt. In starting a new business or expand a business which has been running for the first time to do an analysis of the potential of the business. The amount of funds expended to build a business and a high probability of failing to make the need for research to determine the potential to make profit from the new venture in the long run. The final project will talk about potential business of Garam Manis Company in the aspects of market, technology and finance. Then the ended by conclusions and recommendation for Garam Manis Company. As a conclusion, Garam Manis Company have potential business because based on the analysis of market size, Garam Manis Company has a vast potential market that is a total of 3,015 of textiles, washing and water treatment company in Bandung. when seen from the analysis of the financial aspects of NPV for Garam Manis Company is positive ie 2185594509> 0, then by using the assumption of interest is 20% and 21%, IRR calculation results for Garam Manis Company is 20.0017% and that means IRR> MARR (20% ), so that this project can be said to be potentially. Payback Period is based on the calculation that the author has done, Garam Manis Company wills payback in 3 years, 4 months, 24 days. From the analysis that has been done, it can be concluded that the business is being run by Garam Manis Company is potentially.Keyword: Industrial salt, imitability, complementary assets, textiles, water treatment